FORMAÇÃO DE PROFESSORES EM SERVIÇO: UMA EXPERIÊNCIA DA REDE MUNICIPAL DE EDUCAÇÃO DE SÃO PAULO INICIADA NO GOVERNO ERUNDINA - Loureiro, Emília Marlene Morgado (2014)
This research deals with the policy for continuing education in teaching service implemented between 1989 and 1992 in the city of São Paulo, during the administration of Mayor Luiza Erundina, with Professor Paulo Freire as head of the Municipal Department of Education in the initial years of hers management. Such policy marked the beginning of the consolidation of achievements, as the result of many Brazilian educators long struggle for changes in Brazilian education. Erundina and Freire represented the possibility of achieving structural changes in education, in a period of great political effervescence of brazilian society. The conquest of space for training at the school in a democratic manner and with the participation of teachers responded to a major demand of that fight. For better understanding of the implementation of this teacher education policy process, we conduct a qualitative research based on documents and literature followed by a field survey with a small set of questions that served as a starting point for conducting an epistemological circle, involving educators who somehow participated in this policy. In this way, we attempted to compose an overview of the concepts that gave support to that policy, allowing an analysis of the actions that have been developed.